2001
DOI: 10.1037/0012-1649.37.4.533
|View full text |Cite
|
Sign up to set email alerts
|

Infant temperament and the brainstem auditory evoked response in later childhood.

Abstract: Brainstem auditory evoked responses (BAERs) were evaluated on 10-12-year-old children (N = 56) who had been classified as high or low reactive to unfamiliar stimuli at 4 months of age. BAER measurement was selected because high reactive infants tend to become inhibited or fearful young children, and adult introverts have a faster latency to wave V of the BAER than do extroverts. Children previously classified as high reactive at 4 months had larger wave V components than did low reactive children, a finding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 32 publications
0
15
0
2
Order By: Relevance
“…The high reactives also had significantly larger wave 5 values ( r (125)=2.87, P <0.05), and this variable best separated the two temperamental groups. 19 …”
Section: Resultsmentioning
confidence: 99%
“…The high reactives also had significantly larger wave 5 values ( r (125)=2.87, P <0.05), and this variable best separated the two temperamental groups. 19 …”
Section: Resultsmentioning
confidence: 99%
“…The concept of temperament is also supported by animal researchon he one hand by showing that basic human behavioral traits can also be present in primates 83 and on the other hand by the findings of structural and functional differences in the CNS in relationship to temperament in children [84][85][86][87] . Work about temperament in dogs also indicates a shared four-dimensional structure in humans and dogs corresponding to Cloninger's description 88 .…”
Section: Temperament and Personalitymentioning
confidence: 87%
“…Notably, ERP studies have shown that brainstem (wave V) responses to simple auditory stimulation are increased in patients with panic disorder (Knott et al, 1994) and children with high dispositional anxiety (Woodward et al, 2001). These findings suggest that anxiety boosts auditory signaling very early (~10 ms) in the afferent pathway at the relatively primitive level of the inferior colliculus.…”
Section: Sensory-perceptual Processingmentioning
confidence: 99%